Peningkatan Minat Dan Hasil Belajar Matematika Siswa Menggunakan Problem Based Instruction Pada Materi Garis Dan Sudut Siswa Kelas VIIB Di SMP Taman Dewasa Ibu Pawiyatan Yogyakarta - Yoviani Minarti Rauf; Benedictus Kusmanto (UNION: Jurnal Ilmiah Pendidikan Matematika, 2018)
This study aims to describe the process of learning with Problem Based Instruction (PBI) model in order to increase interest and learning outcomes of students of class VII B SMP Taman Dewasa Ibu Pawijayatan Yogyakarta in the even semester of the academic year 2016/2017. The research method used in this research is Classroom Action Research. The results showed that the interest and results of learning mathematics students with the model of learning Problem Based instruction (PBI) has increased. The average value of cycle I 65.8 and the average value of cycle II 72.6. While the percentage of interest for the cycle I 80% and percentage interest rate for cycle II 87%.